Judge Independence in Criminal Imposition Below The Special Minimum Case of The Criminal Action of Corruption - Shafira, Maya; Achmad, Deni; Pitaloka, Diva; Jumadi, Joko; Silvia Riani, Rahmawati; Ernawati, Ninin (Journal of Law and Policy Transformation, 2023)
The inclusion of a specific minimum crime in the Law on the Eradication of Criminal Acts of Corruption is intended to prevent a very striking disparity of sentencing, both for the same case in the context of deelneming, as well as for different cases but the types of offenses involved. the ratio decidendi of the judge's decision that imposes a criminal under a special minimum in corruption cases. Judges who impose criminal penalties under the special minimum criminal threat on decisions on corruption cases, the authors of the analysis assume that the degree of guilt of the accused is not directly proportional to its dangerous act and will be very disproportionate between the act and the punishment that will be given to the defendant of a criminal act of corruption, so that in the name of "Justice" the judge carries out contra legem or legal breakthroughs against the provisions of the special minimum criminal threat in the Law on the Eradication of Criminal Acts of Corruption. The independence of judges and the conviction of judges in imposing criminal penalties under a special minimum penalty in cases of criminal acts of corruption are reflected in legal reasoning in the judge's decision.